Biossensor baseado em peroxidase de atemóia imobilizada em nanoargila modificada para biomonitoramento de glifosato - Oliveira, Grasielli Correa de (2012)
The use of pesticides in agriculture is a necessary practice to control pests, diseases or weeds to achieve high productivity and thereby meet the growing demand for food. The pesticides used today have a very broad utilization, and there are several herbicides of broad spectrum of action, such as glyphosate (N-phosphonomethyl glycine) cited as the largest selling herbicide around the world. Due to the widespread use of glyphosate, the development of methods of analysis for the detection and quantification of the herbicide in different matrices is of paramount importance. There are difficulties in establishing simple methods for determination of glyphosate because of its ionic character, low volatility, high solubility in water and no chromophoric groups. The enzymatic biosensors appear as an alternative method for the detection of glyphosate. They can be applied using the inhibitory effect of pesticides on the most enzyme activity. A biosensor based on atemóia (Annona cherimola, Mill x Annona squamosa, I.) peroxidase immobilized on nanoclay modified (montmorillonite modified with groups aminopropyltriethoxysilane and octadecylamine) was constructed for the determination of glyphosate in water samples. The biosensor was prepared from a carbon paste containing 94.5 mg of graphite powder, 10.5 mg of multilayer carbon nanotube, 60.0 mg of mineral oil and 20.0 mg of immobilized peroxidase to the nanoclay. The square wave voltammetry (SWV) was used for optimization and application of the biosensor and various parameters (concentration of enzyme and hydrogen peroxide, pH, frequency (f), pulse amplitude (DEp) and scan increment (DEs) were investigated to evaluate the best experimental conditions. The best performance was achieved for the biosensor using 0.1 mol L-1 of phosphate buffer solution (pH 7.0), 1.9 x 10-4 mol L-1 of hydrogen peroxide, and the VOQ, f of 30 Hz, DEp of 50 mV and DEs of 4 mV. The reproducibility and repeatability of the biosensor showed RSD% of 8.7 % and 5.5 % respectively. The linear response of the biosensor is between 0.10 and 4.55 mg L-1 with an LD of 0.03 mg L-1 and LQ of 0.09 mg L-1. The average recovery of glyphosate in water samples ranged from 94.9 to 108.9 %, indicating good accuracy of the biosensor. According to Student's t test at a confidence level of 95 %, there was no significant differences between the recoveries using the biosensor and added glyphosate concentrations in water samples. However, for the results of ionic chromatography (IEC), there were significant differences between added and found concentrations of glyphosate in the samples. The stability of the biosensor was measured over a period of eight weeks and response of the biosensor remained within the statistical control limits. Finally, success in enzyme immobilization together with the contribution of carbon nanotubes provide an efficient biocatalyst. The biosensor constructed from this material combined with the inhibitory effect of glyphosate on the enzyme activity was found to be satisfactory for the determination of this herbicide in water samples. Moreover, the construction of this biosensor is simple and relatively low cost.